Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Risiko Bisnis terhadap Struktur Modal (Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Alia Aprilia; Retno Fuji Oktaviani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to analyze the profitability, liquidity, size of the company, and business risk to the capital structure. The study consists of four independent variables: profitability that is proxy with Return on Equity, liquidity that is Proxy with Current Ratio, Firm Size, and Business Risk proxy in BRSIK, and for the dependent variable: Capital Structure measured with Debt to Equity Ratio. In this study there were 41 companies meeting the criteria of 92 total observations with research objects on property and real estate companies registered in the BEI in the period 2019-2023. The methods used in this study consist of Classical Assumption Test, Correlation Coefficient Analysis Test, Dual Linear Regression Analysis Trial, Determination Analysis (R2), F Test and T Test. While the data analysis method used is double linear regression with a significance of 0.05 using Statical Product and Service Solution (SPSS) Version 22.0. The results of this study indicate that profitability does not have a significant effect on the Capital Structure. Liquidity has a positive and significant impact on Capital Structures. The size of the Company has a significant and positive impact on capital Structure and Business Risk has a negative and non-significant effect on capital structure.